Pengaruh Latihan Zig-Zag Menggunakan Metode Interval dan Metode Repetisi Terhadap Kelincahan Pemain Sepakbola - Rizki Mubaraq; HerdiansyahAgus; Yudhi Esa Saputra; Siti Nur Annisa (Universitas Tangerang Raya, 2022)
In this study, the authors examine the zig-zag exercise with interval training methods and repetition training methods to increase agility. The purpose of this study was to determine the effect of zigzag training with interval and repetition training methods on the agility of soccer players. The method used in this research is the experimental method. The population in this study were students of the Bandung Coerver Coaching Team, while the sample used in this study consisted of 22 students of the Bandung Coerver Coaching Team. This study was conducted for 8 weeks with a frequency of exercise 2 times a week. Based on the processing and analysis of the data obtained, the results of the study were that there was no significant increase in the two training methods on the agility of football players. When compared, there is a difference in the improvement of these two training methods. Based on the results of this study, the authors recommend that the repetition method be an option as a method to improve the agility of football players.